Crystal structure of (1,4,7,10,13,16-hexaoxacyclooctadecane-κ6O6)-((Z)-N,N′-bis(2-(dimethylamino)phenyl)carbamimidato-κ1N)potassium(I) - Hong Dabeen; Lee Kyounghoon (Zeitschrift für Kristallographie - New Crystal Structures)
C29H45KN4O7, P21/c (no. 14), a = 9.0016(2) Å, b = 23.5942(7) Å, c = 14.9186(4)Å, β = 102.509(1), V = 3093.28(14) Å3, Rgt = 0.049, wRref = 1270, T = 100K.